2020
DOI: 10.3390/ma13143229
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size and Phase Transformation Behavior of TiNi Shape-Memory-Alloy Thin Film under Different Deposition Conditions

Abstract: TiNi shape-memory-alloy thin films can be used as small high-speed actuators or sensors because they exhibit a rapid response rate. In recent years, the transformation temperature of these films, manufactured via a magnetron sputtering method, was found to be lower than that of the bulk alloys owing to the small size of the grain. In this study, deposition conditions (growth rate, film thickness, and substrate temperature) affecting the grain size of thin films were investigated. The grain size of the thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The grain sizes of the 200 nm, 300 nm, and 400 nm molybdenum carbide films are 9.1 nm, 11.4 nm, and 14.9 nm, respectively. Bae et al [14]have reported the similar result for TiNi shape-memory-alloy thin films deposited by magnetron sputtering, the grain size increased as film thickness increased and corresponded to the crystallinity. Takagi et al [15] reported that high-energy Ar + ions can produce a thermal effect by bombarding the substrate during the deposition process.…”
Section: Resultsmentioning
confidence: 54%
“…The grain sizes of the 200 nm, 300 nm, and 400 nm molybdenum carbide films are 9.1 nm, 11.4 nm, and 14.9 nm, respectively. Bae et al [14]have reported the similar result for TiNi shape-memory-alloy thin films deposited by magnetron sputtering, the grain size increased as film thickness increased and corresponded to the crystallinity. Takagi et al [15] reported that high-energy Ar + ions can produce a thermal effect by bombarding the substrate during the deposition process.…”
Section: Resultsmentioning
confidence: 54%